The vitamin B12 levels in type 2 diabetes mellitus patients on metformin and not on metformin - Dasarathan, Ramesh; Velayudham, Rajendran; Krishnan, Haridoss; S., Senthilkumar (International Journal of Advances in Medicine, 2021)
Background: Type 2 diabetes mellitus (T2DM) is one of the major global public health concerns, metformin is one of the most widely used drugs and considered as first-line therapy for management of T2DM. Vitamin B12 malabsorption is observed in patients on metformin therapy leading to biochemical and clinical vitamin B12 deficiency. The aim of the current study was to assess the relationship between metformin therapy and development of vitamin B12 deficiency. Methods: Current observational cross sectional study was conducted at Madras medical college and Rajiv Gandhi Government general hospital. Serum vitamin B12 and other blood investigation parameters of T2DM patients, on metformin therapy for long duration (6 months or more than 2 years) were measured and correlated with vitamin B12 levels of T2DM patients not on metformin therapy. Patients were given appropriate treatment and were regularly followed up. Results: Results of the current study findings depicted that significant difference was observed in percent haemoglobin, total blood cells, platelet count, mean corpuscular volume (MCV) and albumin values of patients on metformin therapy when compared to patients who were not on metformin therapy. Study findings also revealed that substantial difference in vitamin B12 deficiency was observed in T2DM patients based on the duration of metformin therapy. Conclusions: Current study revealed that, metformin therapy for 2 years or more, can lead to significant vitamin B12 deficiency which is also associated with macrocytosis. It was concluded that longer the duration of metformin therapy, more significant would be vitamin B12 deficiency.